PERANAN POLISI KHUSUS KEHUTANAN DALAM UPAYA MENCEGAH DAN MENANGGULANGI PENEBANGAN LIAR(ILLEGALLOGGING) STUDI DI KECAMATAN MOYO HILIR KABUPATEN SUMBAWA - ABDUL HAMID; IDI AMIN (GANEC SWARA, 2021)
The research was conducted with the aim of knowing and understanding the role of the special forestry police in preventing and tackling Illegal Logging in the forest area of Moyo Hilir District, Sumbawa Regency to find out, analyze the obstacles faced by the special forestry police in preventing and overcoming Illegal Logging. (Illegal Logging) in the forest area of Moyo Hilir District, Sumbawa Regency.The role of the forest police in preventing and tackling illegal logging (Illegal Logging) has not been as effective as expected, it is proven that illegal logging continues, especially in perhutani forest areas (teak forest). This happened because when Perhutani left the teak forest (HTI) it was not handed over directly to the local government (Sumbawa Forestry Service) but was directly handed over to the central government so that here the Sumbawa Forestry Service was not authorized to maintain and protect the teak forest area. Meanwhile, the obstacles faced by the forest police in preventing and tackling illegal logging are: the provisions of the law are not clear, Human Resources are still lacking, supporting facilities and infrastructure are not sufficient, the condition of the community around the forest and inadequate funds.